Attenuating heat-induced cellular autophagy, apoptosis and damage in H9c2 cardiomyocytes by pre-inducing HSP70 with heat shock preconditioning. (May 2013) - Hsu, Shu-Fen; Chao, Chien-Ming; Huang, Wu-Tein; Lin, Mao-Tsun; Cheng, Bor-Chih
Abstract Purpose: We sought to assess whether heat-induced autophagy, apoptosis and cell damage in H9c2 cells can be affected by pre-inducing HSP70 (heat shock protein 70). Materials and methods: Cell viability was determined using 3-(4, 5-dimethyl-thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide staining and a lactate dehydrogenase assay. Apoptosis was evidenced using both flow cytometry and counting caspase-3 positive cells, whereas autophagy was evidenced by the increased LC3-II expression and lysosomal activity. Results: The viability of H9c2 cells was temperature-dependently (40–44 °C) and time-dependently (90–180 min) significantly (p < 0.05) reduced by severe heat, which caused cell damage, apoptosis and autophagy. Heat-induced cell injury could be attenuated by pretreatment with 3-methylademine (an autophagy inhibitor) or Z-DEVD-FMK (a caspase-3 inhibitor). Neither apoptosis nor autophagy over the levels found in normothermic controls was induced in heat-shock preconditioned controls (no subsequent heat injury). The beneficial effects of mild heat preconditioning (preventing heat-induced cell damage, apoptosis and autophagy) were significantly attenuated by inhibiting HSP70 overexpression with triptolide (Tripterygium wilfordii) pretreatment. Conclusion: We conclude that pre-inducing HSP70 attenuates heat-stimulated cell autophagy, apoptosis and damage in the heart. However, this requires in vivo confirmation.